IMPACT OF ORGANIZATIONAL CHANGE ANTECEDENTS ON JOB SATISFACTION: THE MEDIATING ROLE OF PERCEIVED FULFILLMENT OF PSYCHOLOGICAL CONTRACT - Akhtar, Muhammad Naseer; Long, Lirong; Nazir, Sajjad (European Scientific Journal, ESJ, 2015)
The relationship between employee and employer has faced revolutionary shifts in the past decades, causing radical changes in psychological contracts. This study explores the impact of organizational change antecedents as cause (type of change, personal impact of change, frequency of change and successfulness of past changes) on the perceived fulfillment of organizational obligations as content/mediating variable (job content, career development, social atmosphere, organizational policies, work life balance, and rewards) and job satisfaction as consequence. Furthermore, this review offers propositions based on current literature for further in-depth empirical investigations to find out the combined effects of organizational change antecedents, perceived fulfillment of organizational obligations and behavioral outcomes with academic and practical relevance.